STATUS GIZI DAN DEFISIENSI KALSIUM PADA ANAK BALITA DI INDONESIA: SAMPEL RISKESDAS 2018 - Arifin, Aya Yuriestia; Rimbawan, Rimbawan; Riyadi, Hadi; Retiaty, Fifi; Nurjanah, Nunung; Julianti, Elisa Diana; Nurhidayati, Nuzuliyati (Persagi, 2024)
Calcium is believed to play a role in growth, especially in children under five, and contributes to malnutrition issues in Indonesia. However, national-scale data are very limited to delve deeper into this matter. The study aims to examine the calcium status of children in Indonesia and their nutritional status, including stunting and underweight. A cross-sectional study design using secondary data from the 2018 Basic Health Research (Riskesdas) and Study of Nutrition Status of Children Under Five and School-Aged Children 2021, including serum calcium concentration data and anthropometric measurements of body length and body weight. The study subjects were children aged 0-59 months, totaling 550 samples. The study results show the mean value of calcium concentration was 10.00±1.10 mg/dL. As many as 8.2 percent of children experienced deficiency with calcium concentration <9.0 mg/dL. The proportion of stunted and underweight children was 23.27 percent and 9.82 percent, respectively. The average calcium concentration in stunted and underweight children was not significantly different from the normal scores of HAZ and BAZ in children. Calcium status, along with factors such as age and sex, did not show a relationship with nutritional status indicators like height-for-age (HAZ) and weight-for-age (WAZ). Although the prevalence of calcium deficiency among toddlers in Indonesia is relatively low, there are still children with calcium concentrations significantly below the normal range. Further studies are needed to figure out the contribution of calcium to children's growth.